Implementasi Manajemen Rekam Medis Digital dalam Pengabdian kepada Masyarakat di Layanan Kesehatan Gigi dan Mulut - Sadikin, Muhammad; Putri, Dini Ridha Dwiki; Syamanta, Arbana; Liswanty, Ina; Masyitah, Emi; Batubara, Rini Oktari (Publikasi Pengabdian Masyarakat, 2025)
Dental and oral health services that still rely on manual recording systems often face various problems, such as difficulty in searching for data, the risk of losing information, and inefficiency in the service process. This study aims to implement a digital medical record management system to improve the efficiency and quality of services in dental and oral clinics. The methodology used includes field observations, interviews with clinic staff, and training and assistance in implementing the digital system. Based on the results of the study, the implementation of this digital system has succeeded in accelerating the patient administration process, increasing data security, and facilitating the management of more structured and integrated patient information. In addition, clinic staff reported increased efficiency in administrative work, while patients felt more satisfied with faster and more organized services. In conclusion, the implementation of a digital medical record management system has proven effective in overcoming the constraints of manual data management and improving the quality of dental and oral health services. This study can be a reference for other clinics that want to carry out digital transformation in medical record management.